Developing flat field extensive animation media by using VBA for powerpoint to improve higher order thinking skills in vector analysis - M Bernard; E Senjayawati (Pascasarjana Universitas Pendidikan Indonesia, 2020)
Development of extensive animation media for the concept of moving images developed by students creative ideas, through extensive field analysis of various forms converted into rectangular shapes through several ways to use VBA for PowerPoint. The language of this program helps students to make the thinking process they do not need to memorize material related to vector analysis material about student thinking material which is part of the VBA language program with new ideas for students. Indicators that determine highlevel thinking skills are 1) analysis, identifying concepts and being able to link concepts 2) Evaluating, students try to make steps systematically 3) Creating, student-oriented students to develop broad-based flat animation media by applying vector analysis into VBA for PowerPoint languages. The research method is Research and Development with 5 stages namely Analysis, Design, Development, Implementation, and Evaluation. For the assessment of media development in the first stage validated by media experts and material experts and for the second stage validated by users or students.